2017
DOI: 10.1111/jog.13355
|View full text |Cite
|
Sign up to set email alerts
|

Primary peritoneal psammocarcinoma

Abstract: Psammocarcinoma is a rare low-grade serous carcinoma arising either from ovary or peritoneum and is characterized by extensive psammomatous calcifications and invasion of surrounding structures. Prognostically, psammocarcinoma resembles borderline serous tumor and has a much more favorable outcome than the common serous carcinoma of ovary and peritoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…15 Calcified leiomyomatosis peritonealis disseminata (LPD), an infrequent subtype of leiomyomatosis occurring amongst young women with history of myomectomy, is another differential diagnosis of PPP. 16 We could rule out this diagnosis since our patient was 74 years-old with no history of myomectomy.…”
Section: Discussionmentioning
confidence: 90%
“…15 Calcified leiomyomatosis peritonealis disseminata (LPD), an infrequent subtype of leiomyomatosis occurring amongst young women with history of myomectomy, is another differential diagnosis of PPP. 16 We could rule out this diagnosis since our patient was 74 years-old with no history of myomectomy.…”
Section: Discussionmentioning
confidence: 90%
“…15 Calcified leiomyomatosis peritonealis disseminata (LPD), an infrequent subtype of leiomyomatosis occurring amongst young women with history of myomectomy, is another differential diagnosis of PPP. 16 We could rule out this diagnosis since our patient was 74 years-old with no history of myomectomy.…”
Section: Discussionmentioning
confidence: 90%
“…3 Chemotherapy is thought to have a poor efficiency in PPP. 16 However, follow-up adjuvant chemotherapy is required, at least for residual diseases and for PPP with aggressive behavior like in the case reported by Akbulut et al 7,21 Given their rarity, we do not dispose enough elements to judge the scalability of PPPs. However, PPP is likely to have a high potential towards peritoneal recurrence, even after suitable treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian primary psammocarcinoma has been classified as a subtype of serous carcinoma with a relatively good prognosis. 1,2 On the other hand, it has been reported that the presence and extent of sand grains do not correlate with prognosis. 4,5 On imaging examination, although CT scan exhibits a large amount of calcification in the ovarian tumor, it is very difficult to rule it out from other benign calcified diseases such as calcified leiomyoma, Brenner tumor, and fibrothecoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many psammoma bodies are found in tumor tissue, and their prognosis is relatively good. 1,2 We report a case of primary ovarian serous psammocarcinoma in which preoperative computed tomography (CT) examination of the abdomen was useful for diagnosis.…”
Section: Introductionmentioning
confidence: 99%